2012
DOI: 10.1159/000343721
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Glutamate Modulates Porcine Retinal Development in vitro

Abstract: Embryogenesis of the retina is a complex event orchestrated by a multitude of physical and biochemical signals. To study the impact of intrinsic developmental cues, the retinal tissue can be isolated in culture which also enables modulation of normal development for other purposes, i.e. transplantation of specific neuronal cell types. In the present experiment, cell type development of immature porcine retinal tissue kept in culture was explored using specific immunohistochemical markers. Retinal explants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The overall morphology and immunohistochemical characteristics of the normal adult porcine retina has been well described previously but will be summarized here [4][5][12][13][14][15][16][17][18]. Hematoxylin and eosin staining of in vivo controls revealed clearly defined nuclear and plexiform layers as previously described (Fig.…”
Section: In Vivo Controlsmentioning
confidence: 75%
See 1 more Smart Citation
“…The overall morphology and immunohistochemical characteristics of the normal adult porcine retina has been well described previously but will be summarized here [4][5][12][13][14][15][16][17][18]. Hematoxylin and eosin staining of in vivo controls revealed clearly defined nuclear and plexiform layers as previously described (Fig.…”
Section: In Vivo Controlsmentioning
confidence: 75%
“…In addition, it was believed that the support provided by the culture membrane would mimic physical RPE-outer segment interaction in vivo. This approach has been used successfully for the study and modulation of immature tissue which has been found to survive well with several signs of normal development [9][10][11][12][13]. In contrast, as mentioned above, isolated adult retinal sheets cultured under standard conditions, display gliosis and neuronal degeneration very early [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used successfully for the study and modulation of immature retinal tissue, which has been found to survive well and even displays several signs of normal development [Caffé et al, 1989;Ogilvie et al, 1999Ogilvie et al, , 2000Engelsberg and Ghosh, 2007;Ghosh et al, 2012]. Cultures of adult retinal tissue, on the other hand, have been found to be much more limited in their ability to survive in vitro.…”
Section: Ex Vivo Retina Explant Culturesmentioning
confidence: 99%